Daughters and the paternal function in the absence of the father - Kamau, Gloria Njeri (My University, 2018)
Given the increasing number of non-traditional households’ such as single mother-headed households in the South African context, this research focused on the absence of fathers in relation to child development which is significant social problem within society. It explored the experiences of daughters with absent fathers in South Africa with regards to the paternal function. It also explored daughters’ experiences around the performance or non-performance of the paternal function and their thoughts on the potential impact of the absent father in their lives. The research study was framed using a psychoanalytic lens with a focus on the unconscious. The participant group consisted of seven young black women in single mother headed households with absent fathers. Semi structured interviews were used to collect the data. The data was analysed using interpretive thematic analysis couched within psychoanalytic orientation. The key themes that emerged were daughters perceived their childhood as ‘normal’ and utilised various defence mechanisms to protect themselves from the hurt of father loss. It was also evident that there was a longing for the ‘real father’. Furthermore, the absence of the father was seen to impact their identity and relationships with men. In terms of implications, the study demonstrated the need for research that challenges and expounds on theoretical concepts that may require reconceptualization given the changing contexts. It also provided some evidence for clinical work in terms of tailoring appropriate therapeutic interventions.
A research project submitted in partial fulfillment of the requirements for the degree of Master of Arts in Community-Based Counselling Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, October 2018
Keywords: Mothers and daughters; Single-parent families.; Mother and child